The global implications of a Russian gas pivot to Asia - Steve Pye; Michael Bradshaw; James Price; Dan Zhang; Caroline Kuzemko; Jack Sharples; Dan Welsby; Paul E. Dodds (Nature Communications)
Abstract Recent years have seen unprecedented shifts in global natural gas trade, precipitated in large part by Russia’s war on Ukraine. How this regional conflict impacts the future of natural gas markets is subject to three interconnected factors: (i) Russia’s strategy to regain markets for its gas exports; (ii) Europe’s push towards increased liquified natural gas (LNG) and the pace of its low carbon transition; and (iii) China’s gas demand and how it balances its climate and energy security objectives. A scenario modelling approach is applied to explore the potential implications of this geopolitical crisis. We find that Russia struggles to regain pre-crisis gas export levels, with the degrees of its success contingent on China’s strategy. Compared to 2020, Russia’s gas exports are down by 31–47% in 2040 where new markets are limited and by 13–38% under a pivot to Asia strategy. We demonstrate how integrating energy geopolitics and modelling enhances our understanding of energy futures.